VOCABULARY TEACHING - Nina Dwiastuty (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
By the time students get to upper intermediate level or beyond, we can be sure that some of them will know some of the words we are asking them to focus on. The more the students master the vocabulary the better they performances in all aspect of English language. Having a limited vocabulary is also a barrier that prevents students from learning a foreign language. Vocabulary is the stock of words used in language. Vocabulary as a means of thought, expression, interpretation and communication. Vocabulary also basic to communication, when someone wants to follow in the conversation, so he or she must understand the words used by the speakers. As language teachers, we must arouse our students’ interest in words, especially in the early stages of learning, is a prerequisite for later proficiency in the language.Keywords: Vocabulary and teaching.